Flexural behaviour of damaged concrete T-beams reinforced with ultra-high performance concrete filling - Huang, Shuai; Xi, Yonglei; Li, Xin; Men, Pengfei; Wu, Gangan (Frontiers in Materials, 2024)
To improve the flexural performance of damaged reinforced concrete T-beams, a method of filling ultra-high performance concrete (UHPC) in the damaged area was adopted. Experimental studies were conducted on two UHPC-reinforced concrete T-beams with different lengths of damaged areas and one undamaged concrete T-beam as a reference. Crack distribution, failure modes, cracking loads, flexural capacities, and strain variation of the specimens were analyzed. Subsequently, a nonlinear finite element (FE) model of the UHPC-reinforced T-beam was developed using ABAQUS, and the FE model results were compared with the experimental results to validate the accuracy of the FE simulation method. The results indicated that the two UHPC-reinforced T-beams exhibited a similar flexural failure process to the undamaged T-beam. The longitudinal tensile strain distribution at the mid-span section showed that the composite section formed by the filling of UHPC in the damaged region still adhered the assumption of the planar section. Owing to the excellent bond performance between UHPC and the existing concrete, the main cracks of the UHPC-reinforced T-beams appeared in the chiseled area, and the crack widths of the UHPC-reinforced T-beams under the same load were smaller than those of the reference T-beam. Overall, the reinforcing method of filling UHPC in the damaged region can restore or even enhance the flexural performance of the damaged reinforced concrete Tbeams.